Tobacco Smoking and Dental Periapical Condition in a Sample of Saudi Arabian Sub-Population - Laila A. Bahammam, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The aim of this study is to investigate the possible influence of smoking on the prevalence of periapical lesions. A total of 98 individuals (20 smokers and 78 non smokers) participated in the study. The periapical condition was assessed radiographically for each dental root. The following information was recorded on a structured form for each subject: (a) number of teeth present; (b) number of teeth with root fillings (treated teeth) having identifiable periapical lesions and (c) number of teeth without root fillings (untreated teeth) having identifiable periapical lesions. The data was statistically analyzed using "t" test at p < 0.05. There was no significant influence of smoking on the prevalence of apical periodontitis in the presence or absence of endodontic treatment. The results of this study do not provide support to the assumption that tobacco smoking is associated with apical periodontitis.